2021
DOI: 10.1001/jamanetworkopen.2020.36676
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Caregiver Strain and Self-Care Among Caregivers With Diabetes

Abstract: IMPORTANCE Caregiver strain has been shown to be associated with adverse effects on caregivers' health, particularly among those with cardiovascular disease. Less is known about the association of caregiver strain with health behaviors among caregivers with diabetes, a disease that requires a high degree of self-care. OBJECTIVE To examine the association between caregiver strain and diabetes self-care among caregivers with diabetes. DESIGN, SETTING, AND PARTICIPANTS This cohort study was conducted between July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Also, in a study in the United States, 45.9% of caregivers reported moderate caregiver strain [ 8 ], which is consistent with the results of the present study [ 28 ]. .Also, in a study in the United States, 45.9% of caregivers reported moderate caregiver strain [ 8 ], which is consistent with the results of the present study. Zhang et al in a study using the CSI found that more than 50% of caregivers of dementia patients experienced high levels of caregiver strain, which is not consistent with the present study [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Also, in a study in the United States, 45.9% of caregivers reported moderate caregiver strain [ 8 ], which is consistent with the results of the present study [ 28 ]. .Also, in a study in the United States, 45.9% of caregivers reported moderate caregiver strain [ 8 ], which is consistent with the results of the present study. Zhang et al in a study using the CSI found that more than 50% of caregivers of dementia patients experienced high levels of caregiver strain, which is not consistent with the present study [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Shafiezadeh et al found that caregiver strain was higher than average in family caregivers of older adults with Alzheimer's disease [28]. Also, in a study in the United States, 45.9% of caregivers reported moderate caregiver strain [8], which is consistent with the results of the present study [28]. .Also, in a study in the United States, 45.9% of caregivers reported moderate caregiver strain [8], which is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study also showed that only 18.4% of T2D patients’ caregivers report high level of strain. 19 The observed difference likely related to the screening tool difference along with the caregiver age in our study. Another study showed that 42% of the caregivers had little to no stress and the difference observed may be related to the caregiver’s relation to patients as 92.6% of our study caregivers were patient’s offspring compared with 40%.…”
Section: Discussionmentioning
confidence: 66%
“…2,5 Metabolic conditions, such as metabolic syndrome or diabetes mellitus, are also increasingly common in 21st century patient care, and these types of conditions present unique challenges for individuals who wish to remain in their homes. 6 More severe progressions of these and other diagnoses may have significant impact on functional mobility, requiring assistance from informal caregivers for activities such as transfers, gait, stairs, wheelchair use, among other tasks. 7 For some patients, there is significant physical assistance required with lifting such individuals within a home healthcare environment, including the regular execution of activities such as bathing, bed mobility, and wheelchair propulsion.…”
Section: Introductionmentioning
confidence: 99%